2015
DOI: 10.3389/fpsyg.2015.00703
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of national wealth and skill influence pay expectations: replicating global hierarchy on a microscale

Abstract: In highly multicultural societies, the economic status hierarchy may come to mimic the hierarchy of global wealth, reinforcing social inequality by tying pay scales to national wealth. We investigated how nationality influences expectations of payment in the UAE. Participants reported how much they expected people to be paid and how much skill they were perceived to have by nationality. They also reported their perceptions of the national wealth of different countries. Participants generally expected Westerner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Specifically, they found that European nationals were paid more than Gulf Cooperation Council (GCC) Arabs, 1 followed by non-GCC Arab, Asian, and African workers. This national hierarchy is also perceived and expected by UAE residents (Maitner & DeCoster, 2015). However, explanations for the national hierarchy varied somewhat by national grouping.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Specifically, they found that European nationals were paid more than Gulf Cooperation Council (GCC) Arabs, 1 followed by non-GCC Arab, Asian, and African workers. This national hierarchy is also perceived and expected by UAE residents (Maitner & DeCoster, 2015). However, explanations for the national hierarchy varied somewhat by national grouping.…”
mentioning
confidence: 82%
“…However, empirical research shows that both ascribed characteristics, such as nationality, and achieved characteristics, such as skill, influence perceptions of and actual differences in salary in the United Arab Emirates (UAE; Maitner & DeCoster, 2015; Tong & Al Awad, 2014). Although strongly connected to its Arab roots, the UAE is a state capitalist society embracing a neoliberal ethos (see Kanna, 2011; Maitner & Stewart-Ingersoll, 2016), and belief in equal opportunity is codified as a citizenship responsibility for Emiratis (Government of the United Arab Emirates, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But this apparent preference is complicated by other aspects of this study. First, while using participants who originated from South Asia (mostly India, Pakistan, and Bangladesh) would not necessarily be problematic in the USA, social distinctions in the UAE between native, national citizens (Emiratis) and non-native residents are substantial, and South Asian women in the UAE tend to hold low-status positions, have low job security, and experience considerable risk if they contravene UAE laws or customs [ 14 ]. In contrast, the majority of Emiratis (males and females) enjoy very high social status in the UAE, and Emirati women habitually wear the hijab in public.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this would not necessarily be problematic for participants in the USA, participants in the UAE would have been non-native, ex-patriate residents with limited residents’ visas due to strict UAE laws concerning citizenship and residency. Moreover, social distinctions between ex-patriate occupants and native Emiratis are substantial in the UAE, and residents from South Asia generally take lower-ranking jobs, occupy lower levels on the social scale, and experience considerably less job security and greater risk of deportation if laws or customs are contravened [ 18 ]. Accordingly, as wearing the hijab is the norm in the UAE amongst native UAE Emirati females, the preference shown by UAE South Asian participants for images of female faces wearing the hijab in the Pasha-Zaidi study may reflect internalized self-preserving deference towards the prevailing Emirati culture.…”
Section: Introductionmentioning
confidence: 99%